Harvesting Success: Strategy Development for Kampoeng Anggrek Agro-Tourism: Keberhasilan Panen: Strategi Pengembangan Agrowisata Kampoeng Anggrek - Tsalits, Askhaarina Aulia; Magfiroh, Illia seldon (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
The research focuses on Kampoeng Anggrek Agritourism, a growing attraction in Kediri City that is seeing an increase in everyday visits, especially on weekends and holidays. The COVID-19 epidemic prompted a brief shutdown, which resulted in shifts in facility maintenance and employee attention, resulting in some deterioration. This study aims to evaluate Kampoeng Anggrek's present Business Model Canvas (BMC) and make recommendations for future improvements. Probability sample was used with the business model canvas approach, with ten participants from the internal and forty from the external aspects of Agrotourism Kampoeng Anggrek chosen using simple random sample. The research resulted in a comprehensive BMC framework, which provided proprietors with a clear picture of the company as well as the capacity to fine-tune each BMC aspect for operational optimization in agritourism operations. This study provides critical insights for stakeholders navigating the changing landscape of agrotourism firms in the face of dynamic external influences such as the COVID-19 pandemic